2000
DOI: 10.1097/00000658-200012000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Two-Stage Hepatectomy: A Planned Strategy to Treat Irresectable Liver Tumors

Abstract: ObjectiveTo assess feasibility, risks, and patient outcomes in the treatment of colorectal metastases with two-stage hepatectomy. Summary Background DataSome patients with multiple hepatic colorectal metastases are not candidates for a complete resection by a single hepatectomy, even when downstaged by chemotherapy, after portal embolization, or combined with a locally destructive technique. In two-stage hepatectomy, the highest possible number of tumors is resected in a first, noncurative intervention, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
444
2
51

Year Published

2002
2002
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 721 publications
(505 citation statements)
references
References 30 publications
8
444
2
51
Order By: Relevance
“…However, LLR can still be performed safely if the surgeon understands the pharmacological profile of the chemotherapeutic agents, chooses appropriate surgical instruments, and perform the proper surgical maneuvers 100. A study of the utility of two‐stage hepatectomy for bilobar multiple liver metastases as proactive curative surgical treatment for unresectable liver metastases101 found that two‐stage LLR drastically reduced development of intra‐abdominal adhesions after first‐stage liver resection and thus simplified second‐stage liver resection, which is considered technically difficult, thereby achieving long‐term outcomes comparable to those for open two‐stage hepatectomy 102, 103…”
Section: Indications and Oncological Outcomesmentioning
confidence: 99%
“…However, LLR can still be performed safely if the surgeon understands the pharmacological profile of the chemotherapeutic agents, chooses appropriate surgical instruments, and perform the proper surgical maneuvers 100. A study of the utility of two‐stage hepatectomy for bilobar multiple liver metastases as proactive curative surgical treatment for unresectable liver metastases101 found that two‐stage LLR drastically reduced development of intra‐abdominal adhesions after first‐stage liver resection and thus simplified second‐stage liver resection, which is considered technically difficult, thereby achieving long‐term outcomes comparable to those for open two‐stage hepatectomy 102, 103…”
Section: Indications and Oncological Outcomesmentioning
confidence: 99%
“…Previous studies have indicated that the size of the FLR should be at least 25 per cent of total liver volume1 or a ratio greater than 0·5 between FLR and bodyweight2 3. Various strategies such as portal vein embolization (PVE)4 and two‐stage hepatectomy5 have been developed to increase FLR and enable surgical therapy in patients otherwise deemed unresectable.…”
Section: Introductionmentioning
confidence: 99%
“…However, the resectability rate does not exceed 25%, being limited by the multiplicity of LM. 1 The results obtained with other therapies, such as systemic or hepatic arterial chemotherapy, radiotherapy, or immunotherapy, still remain disappointing. Therefore, novel therapeutic strategies are needed, of which gene therapy still represents an attractive approach.…”
mentioning
confidence: 99%